Strategic Investments in the Pulp and Paper Industry: A Count Data Regression Analysis - Mats A. Bergman; Per Johansson (The Research Institute of Industrial Economics (IUI), 2000)
This paper analyses the effects of price and market size variables on the investment propensities in the pulp and paper industry. A panel of 15 European countries in the time period 1984 - 1997 is used in the regression analysis. We find the wages, the US/ECU exchange rate, the price of paper and the installed production capacity to be the main determinants of strategic investments in this industry. Our measure of market size have no - or only very small - effects.
Keywords: D24; E22; L11; L73; 330; Lumpy investments; Prices; Market size; Agglomeration; Distance; Investment determinants; Investition; Produktivität; Marktstruktur; Regression; Papierindustrie; Europa